Mitochondrial Dysfunction in Neurodegenerative Disorders - Reeve, Amy K.; Simcox, Eve M.; Duchen, Michael R.; Turnbull, Doug M. (Springer International Publishing : Imprint: Springer, 2016)
This second edition brings together up-to-date contributions from leaders in the field internationally on the various ways in which mitochondrial dysfunction contributes to the pathogenesis of neurodegenerative diseases, including Parkinson's disease, Alzheimer's disease and multiple sclerosis. The reader is guided through the basic functions of mitochondria and the mechanisms that lead to their dysfunction, and on to the consequences of this dysfunction for neuronal function before finishing with the modelling of these disorders and discussion of new potential therapeutic targets. Additional chapters have been added to the book to reflect advances in the field and there are many new contributors and topics, including how mitochondria are degraded and the interaction of the mitochondria with pathologically relevant proteins. Mitochondrial Dysfunction in Neurodegenerative Disorders provides an accessible, authoritative guide to this important area for neurologists; research and clinical neuroscientists; neuropathologists; and residents with an interest in clinical research.